2013
DOI: 10.1177/0731684413494110
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanofiber aerogel production and applications

Abstract: Aerogels are highly porous solids formed by replacing the liquid in a gel by air, without changing the original structure. The present cellulose aerogels are made by sublimating the water from a colloidal suspension of cellulose nanofibers. The nanofibers form three-dimensional networks, crosslinked by hydrogen bonds bridging the surface hydroxyl groups and also by mechanical entanglements between nanofibers. Although the studies on aerogels from cellulose nanofiber hydrogels by freeze-drying reported so far h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 9 publications
(8 reference statements)
0
17
0
Order By: Relevance
“…They found that liquid nitrogen induced the rapid formation of ice crystals, which effectively inhibited the self-agglomeration of cellulose and produced a more uniform and smooth surface structure [83]. Anti-freezing agents [168] and spray freeze-drying techniques [84,169] also rely on an accelerated freezing rate to produce aerogels with a uniform structure. However, there are similar freezing rate and local temperature gradients ahead of the moving solid–liquid interface, such as when freeze-drying thin samples in a fridge while also cooling a big sample.…”
Section: Preparation Of Cellulose Aerogelmentioning
confidence: 99%
“…They found that liquid nitrogen induced the rapid formation of ice crystals, which effectively inhibited the self-agglomeration of cellulose and produced a more uniform and smooth surface structure [83]. Anti-freezing agents [168] and spray freeze-drying techniques [84,169] also rely on an accelerated freezing rate to produce aerogels with a uniform structure. However, there are similar freezing rate and local temperature gradients ahead of the moving solid–liquid interface, such as when freeze-drying thin samples in a fridge while also cooling a big sample.…”
Section: Preparation Of Cellulose Aerogelmentioning
confidence: 99%
“…In principle, aerogels are prepared by replacing the solvent in the hydrogel with air without altering the original structure of the material [11,12]. Two methods, namely Shamskar et al (2016) fabricated CNC aerogel via freeze-drying from raw cotton and cotton stalk and obtained aerogels with specific surface area of 91.47 and 93.89 m 2 /g, respectively [28].…”
Section: Introductionmentioning
confidence: 99%
“…In principle, aerogels are prepared by replacing the solvent in the hydrogel with air without altering the original structure of the material [ 11 , 12 ]. Two methods, namely supercritical drying and freeze-drying, are mostly used for the fabrication of aerogel.…”
Section: Introductionmentioning
confidence: 99%
“…12 There have been many elastomers proven to be effective for PP-LDPE blends, for example, styrene-butadiene-styrene, 13 ethylene-propylene-diene rubber, 14 ethylene-propylene-ethylidene norborene copolymer (EPCAR-847), 15 PE-g-poly(2-methyl-1,3-butadiene), 9 and so on. In addition, one can introduce micro or nanoparticles-such as talc, 16 carbon nanotube, 17 nanoclay, 18 nano-silicon dioxide (nanoSiO 2 ), 19 nanoTiO 2 , 20 SiO 2 / TiO 2 , 21 and cellulose nanofibers 22 -into the blended material to enhance the mechanical properties of a component fabricated by polymer or polymer blends. However, it was often reported that tensile strength, elastic modulus, and stress at break of the blends with a compatibilizer or nanofiller decreased while impact strength and elongation increased and vice versa.…”
Section: Introductionmentioning
confidence: 99%